The problem of container transportation in Klang Valley: a review for 1982-1984 period / Zakaria Ismail - Ismail, Zakaria (1984)
As the scope of this study is confined to the the movement of containers in Klang Valley, it is essential to highlight the activities of the main participants of containerisation. The aim of this Graduation Exercise is to study the operations of individual organisations that are the container terminal operation, the documentation and procedure systems with regards to FCL containers and the hauliers which individually is a link to a huge chain in containerisation.